Metacognitive functions in patients who has obsessive compulsive disorder and major depressive disorder: a controlled study - Yilmaz, Seda; Izci, Filiz; Mermi, Osman; Atmaca, Murad (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2016)
Objective: The aim of this study was to compare metacognitive functions of patients with obsessive compulsive disorder (OCD) and major depressive disorder (MDD) and their relationship to clinical symptoms with those of the control group. Methods: The study included 50 patients with OCD and 50 patients with MDD who were admitted to Firat University, Clinic of Psychiatry and who met the study criteria and 50 healthy controls. The Structured Clinical Interview (SCID-I) for DSM-IV Axis I Disorders, Sociodemographic and Clinical Data Form, and Metacognition Questionnaire-30 (MCQ-30) were administered to patients and control groups; additionally, the Beck Depression Inventory (BDI) and the Beck Anxiety Inventory (BAI) were also administered to patients with MDD whereas the Yale-Brown obsessive compulsive scale (Y-BOCS) and the Obsessive Beliefs Questionnaire-44 (OBS-44) were administered to patients with OCD. Results: Total metacognition scores were found to be significant in both disease groups as compared to the control group. Metacognition subscales of 'uncontrollability and danger' and 'need to control' were significantly higher in patients with OCD, whereas, the subscale of cognitive confidence was signifycantly higher in patients with MDD as compared to the control group. In addition, there was a positive correlation between Y-BOCS subscale of compulsion and need to control, between the OBQ-44 factor of perfectionism/certainty and uncontrollability between danger and the subscale of cognitive awareness in patients with OCD. On the other hand, there was a positive correlation between BDI scores and metacognition subscales of positive belief, cognitive confidence and uncontrollability and danger in patients with MDD. Conclusion: The findings of our study demonstrated significant differences in the parameters of metacognition questionnaire between patients with depression and those with OCD. Future studies are warranted to elucidate the causal relationship of these differences to MDD and OCD.
Majör depresif bozukluk ve obsesif kompulsif bozukluk hastalarında üst biliş işlevleri: Kontrollü bir çalışma
Keywords: major depressive disorder; obsessive compulsive disorder; metacognition